A Statistical Study of Emission and Generation of Wastes Containing Mercury, and Their Treatment in Ukraine - Kobylynska Т. V.; Huseva, N. Yu. (Statistics of Ukraine, 2019)
The situation with emission and management prospects for the wastes containing mercury and its compounds is analyzed, with identifying main sources generating these wastes and their recycling methods. The results of official statistical observations are used for estimating the data on generation and treatment of these wastes; there proposed principal measures aimed at comprehensive implementation of the Minamata Convention on Mercury and approaches to statistical studies on treatment of wastes containing mercury in Ukraine. It is stressed that the problem of constructing the methodology for official statistical observations in the environmental field, first and foremost the one on emissions of pollutants by enterprises and generation, storage and recycling of wastes, mercury and its compounds in particular, still remains unsolved. Finding ways for its solution is an important step towards the improvement of the present-day official statistics in Ukraine, the development of statistical science and practice, because this is a significant determinant of the quality of administrative information at all the levels. The objective of the study is to perform a statistical assessment of emissions and generation of wastes containing mercury and its compounds, and their treatment in Ukraine. An important part of the study is to elaborate the problems outlined in the Minamata Convention on Mercury, in order to ensure the comparability of information for taking decisions on priority setting and strategy making. A statistical assessment of the dynamics and structure of generated emissions of mercury and its compounds, and generated and recycled wastes of these compounds is made. It is emphasized that mercury and its compounds is on the top positions in the nomenclature of substances polluting the environment. It is also emphasized that Ukraine now is one of the countries where issues related with treatment of mercury wastes are not completely regulated at the legislative level, as there are no legally established limitations or bans on use of the products containing mercury and its compounds. The problems related with statistical recording in Ukraine cannot be settled unless a national strategy on treatment of mercury wastes is elaborated, based on the Minamata Convention provisions concerning implementation of the concept of the product life cycle. Besides that, it is necessary to solve the issues of elaborating methodological recommendations on measurement of the amount of mercury released into the environment and treatment of mercury wastes that have adverse effects for human health and environment.